2018
DOI: 10.1002/mp.13112
|View full text |Cite
|
Sign up to set email alerts
|

A deep learning‐based prediction model for gamma evaluation in patient‐specific quality assurance

Abstract: We developed a CNN-based prediction model for patient-specific QA of dose distribution in prostate treatment. Our results suggest that deep learning may provide a useful prediction model for gamma evaluation of patient-specific QA in prostate treatment planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
145
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(150 citation statements)
references
References 27 publications
4
145
1
Order By: Relevance
“…Another example is a comparison with the DL‐based method as an ultimate approach which automatically involves multiple characteristics. Tomori et al analyzed data of composite dose distributions measured using a gafchromic film and obtained a root mean square error of 1.11%, 1.50%, and 2.24% for the 3%/3, 3%/2, and 2%/2 mm tolerances, which were smaller than our results (2.3, 4.1, and 6.7%) by factor of 2, 3, and 3, respectively. Since our data were obtained from the Delta4 system with a 5‐mm pitch detector array, direct comparisons of these results do not provide an exact goal to achieve.…”
Section: Discussioncontrasting
confidence: 83%
See 2 more Smart Citations
“…Another example is a comparison with the DL‐based method as an ultimate approach which automatically involves multiple characteristics. Tomori et al analyzed data of composite dose distributions measured using a gafchromic film and obtained a root mean square error of 1.11%, 1.50%, and 2.24% for the 3%/3, 3%/2, and 2%/2 mm tolerances, which were smaller than our results (2.3, 4.1, and 6.7%) by factor of 2, 3, and 3, respectively. Since our data were obtained from the Delta4 system with a 5‐mm pitch detector array, direct comparisons of these results do not provide an exact goal to achieve.…”
Section: Discussioncontrasting
confidence: 83%
“…The other approach is a direct estimation of the GPR. Our DUP‐based method, the DL‐based method, and the ML‐based method are classified into this direct estimation. This approach utilizes some parameters which have characteristics of the IM beam and good proportionality to the GPR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this measurement‐based QA still requires either setup or beam delivery times and cannot predict unacceptable‐quality plans . Recently, prediction of dosimetric accuracy has been developed as a more efficient patient‐specific QA method than measurement‐based QA . In fact, prediction does not require setup or beam delivery times, leading to increased adoption of IMRT and VMAT in clinical facilities.…”
Section: Introductionmentioning
confidence: 99%
“…Sum et al reported the prediction of beam output and derived MUs using machine learning . In recent years, there is a growing interest in applying machine learning for predicting the gamma passing rate for IMRT . For instance, Valdes et al predicted the gamma passing rate of 498 IMRT plans using 78 parameters, including MU, linac type, and position of multi‐leaf collimator .…”
Section: Introductionmentioning
confidence: 99%